Patient satisfaction and waiting times in the primary health centres of South Chennai - Yenuganti, Vishnu Vardhan; D., Srinivas Rao; P. J., Sasi Kumar; R., Narendranath (International Journal Of Community Medicine And Public Health, 2021)
Background: Patient satisfaction and the out-patient waiting time denotes the extent to which general health care needs of the patients are met to their requirements. This study assesses the quality of health care delivery in three primary health care centres in south Chennai. The main aim was to assess the levels of patient satisfaction and its relation to various components and the waiting time among the patients visiting the primary health centres in south Chennai. Methods: This is a cross sectional study conducted in three primary health centres in the rural part of south Chennai. This study is conducted by face to face interview method using a structured questionnaire on 120 random patients visiting the OPDs of these health centres. The questionnaire included timing pattern associated with the patients visit in the health centre. The collected data is analysed using Chi-square test and is conducted to assess the relationship between different categorical variables. Results: Most of the respondents (66.6%) were highly satisfied with the service provided, treatment and physician care, facilities inside the hospital, and the care of paramedical staff. Hospital cleanliness and Physician care were found to be significant in terms of overall satisfaction, and large number of patients visiting the centre was the most quoted reason for long waiting times with a mean of 45.2 minutes. Conclusions: The longer waiting times can be effectively reduced by employing more doctors and paramedical staff wherever it is required. A proper feedback system by assessing the satisfaction and waiting time is needed in any tertiary health centre to improve the health care delivery.